Elastocaloric effect in polycrystalline Ni50Ti45.3V4.7 shape memory alloy. (February 2018) - Kim, Yanghoo; Jo, Min-Gu; Park, Ju-Won; Park, Hyung-Ki; Han, Heung Nam
Abstract: The elastocaloric effect and functional fatigue life of the polycrystalline Ni50 Ti45.3 V4.7 shape memory alloy have been studied. Temperature changes on rapid loading and unloading of a mechanically trained specimen were directly measured at different compressive stress levels. It was found that the maximum elastocaloric strength was accomplished at the stress corresponding to the end point of a transformation plateau. In the fatigue test, no significant degradation occurred in the elastocaloric cooling ability after 5000 cyclic loadings. Compared to pure NiTi, the present alloy showed improved efficiency and endurance limit of the functional stability. Graphical abstract: